Restricting the advertising of high fat, salt and sugar foods on the Transport for London estate: Process and implementation study. (January 2022) - Meiksin, Rebecca; Er, Vanessa; Thompson, Claire; Adams, Jean; Boyland, Emma; Burgoine, Thomas; Cornelsen, Laura; de Vocht, Frank; Egan, Matt; Lake, Amelia A.; Lock, Karen; Mytton, Oliver; et al.
Abstract: Introduction: One in five UK children aged 10–11 years live with obesity. They are more likely to continue living with obesity into adulthood and to develop obesity-related chronic health conditions at a younger age. Regulating the marketing of high fat, salt and sugar (HFSS) foods and beverages has been highlighted as a promising approach to obesity prevention. In 2019, Transport for London implemented restrictions on the advertisement of HFSS products across its network. This paper reports on a process evaluation of the design and implementation of this intervention. Methods: In 2019–2020, we conducted semi-structured interviews with 23 stakeholders. Interviews with those responsible for implementation (n = 13) explored stakeholder roles, barriers and facilitators to policy development/implementation and unintended consequences. Interviews with food industry stakeholders (n = 10) explored perceptions and acceptability of the policy, changes to business practice and impact on business. Data were analysed using a general inductive approach. Results: Practical challenges included limited time between policy announcement and implementation, translating the concept of 'junk food' into operational policy, the legal landscape, and reported uneven impacts across industry stakeholders. Political challenges included designing a policy the public views as appropriate, balancing health and financial impacts, and the perceived influence of political motivations. Consultation during policy development and close communication with industry reportedly facilitated implementation, as did the development of an exceptions process that provided a review pathway for HFSS products that might not contribute to children's HFSS consumption. Conclusions: Findings suggest that restricting the outdoor advertisement of HFSS foods and beverages at scale is feasible within a complex policy and business landscape. We outline practical steps that may further facilitate the development and implementation of similar policies and we report on the importance of ensuring such policies are applied in a way that is perceived as reasonable by industry and the public. Highlights: Restrictions on HFSS food marketing is a promising public health policy. Practical challenges include defining 'junk food' and navigating the legal landscape. Political challenges included balancing the health and financial impacts of the intervention. Restricting HFSS food advertisement is highly feasible.